Public temporalities. Conflict(s) for momentum - Faure, Antoine (Re-presentaciones: Periodismo, comunicación y sociedad, 2023)
In permanent reconfiguration between its layers, densities, textures, time and its pluralities are an instrument of governance of the public. In a discreet way, sometimes using acceleration, other times dilating or also disguising itself as regularity, it impacts what can be said (or not), from when the word or the decision can be taken, as a matrix of what for and how it should be said. Thus, public temporalities contribute to the construction of perceptible and thinkable forms of a common world, that is, to conventions and norms about the fictions of the public, about subjects and events. The questioning then shifts from representative conceptions of the public and the normative philosophy of freedom of expression to the perception of the public and the conventional discourse on a commons.
Keywords: Temporalities; chronopolitics; momentum; public communication; politicity